Using the Implicit Relational Assessment Procedure (IRAP) to Examine Implicit Gender Stereotypes in Science, Technology, Engineering and Maths (STEM). - Fleming, Katie; Foody, Mairead; Murphy, Carol (Psychological Record, 2020)
Women are often subject to gender stereotyping in the fields of science, technology, engineering, and mathematics (STEM). The Implicit Relational Assessment Procedure (IRAP) was used to determine directionality of any implicit gender-STEM bias detected. In addition, the IRAP was used to explore the possibility of implicit ageism bias, because there is anecdotal evidence of high levels of ageism in the STEM areas. Thus two IRAPs (one with adult pictorial stimuli and one with child pictorial stimuli) were employed to assess implicit gender bias toward STEM with a sample of undergraduates (N = 33). Results indicated a gender STEM bias in both IRAPs and the directionality in both IRAPs was pro-male and not anti-female. Participant gender was not shown to impact results in either IRAP. Gender bias effects were more pronounced in the Adult-IRAP results. Comparison of bias toward older versus young pictorial stimuli was exploratory thus findings are preliminary but may suggest ageism and potential negative interaction effects between age and gender warrant further research.